HUBUNGAN ANTARA KECERDASAN EMOSIONAL DAN TINGKAT RESILIENSI REMAJA DI PANTI ASUHAN - Lismaria " "; Jumaini " "; Erwin " " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract The purpose of this research is to determine the relationship of emotional quotientwith level of resilience adolescents in orphanage. The method used descriptive correlation with cross sectional approach. This research is conducted in 9 orphanages in Pekanbaru, which are Al- Hidayah orphanage, Al-Misqoah orphanage, Insan Permata orphanage, Sri Mujinab orphanage, Muhammadiyah orphanage, As-Showah orphanage, At-Thoibah orphanage, Baiturrahman orphanage, and Al-Istiqlal orphanage, with number of sample 205 respondens that taken use cluster sampling. This research used questionnaire as measuring instrument which has tested the validity and reliability, and chi-square test use for analyzing the data. The result of this research shows that adolescents with high emotional quotienthave high resilience as much as 68,2%, while adolescents with low emotional quotient have low resilience as much as 74,5%. The concluded based on the result of this research that there is a relationship of emotional quotient with level of resilience adolescents in orphanage (p value 0,000 < 0,05), it is suggested to manager of orphanage to facilitate adolescents in developing their emotional quotient so the high level of resilience can be reached. Keyword: Adolescents, emotional quotient, orphanage, resilience.